The Convergence of Positivity: Are Happy People All Alike? - Iliev, Rumen; Bennis, Will (My University, 2022)
More than a century ago Leo Tolstoy noted that happy families tend to be more similar to each other than unhappy families. Was this just a cognitive illusion, driven by his mind’s predisposition to see positive entities as more similar to each other, or did he make a profound observation about the world? If it is true, is the phenomenon limited to happiness, or is it a characteristic of positive traits more generally? This question has received attention in multiple fields, but not in psychology. We ran five studies, testing the more general hypothesis that people who share some positive individual-difference trait are more alike than those who do not (The Convergence of Positivity Hypothesis), and we consistently found empirical support for it. Happier, healthier and richer people were more alike in their personality, values, and in various other domains. The research approach we followed here departs from traditional behavioral science methods and proposes a different level of analysis, where valence and directionality play a central role. We speculate about why this pattern might exist and about the boundary conditions, including whether it extends beyond individual differences to a broader set of complex systems where positivity can be defined.
PsyArXiv Preprints
Keywords: Families and relationships; Health and wellbeing